Improving the way we do action research in quality improvement - Sharon Williams (Production Planning and Control, 2025)
After three decades of action research (AR) there are still questions about its application and contribution in comparison to traditional research methods. The aim of this paper is to explore and critique how two action research frameworks can be employed when improving healthcare processes. We also investigate the role of the Researcher in Residence when using AR in health operations management. Using Problem Resolving Action Research and Collaborative Action Research models we identify the benefits and challenges of conducting AR. To improve the reporting of action research we offer revised guidelines developed within the context of healthcare improvement that will assist both academics and practitioners when undertaking AR. The study also clarifies the important role of the researcher in residence which will assist academics and practitioners by providing consistency to terminology and understanding when undertaking AR research.